Degradation of tartrazine dye from aqueous solution by heterogeneous fenton-like reaction on Fe2O3/SiO2 composite - Tu, Vu Van; Tuan, Vu Anh (Vietnam Journal of Chemistry, 2017)
In this study, Fe2O3/SiO2 composite was prepared by incipient impregnation method for degradation of tartrazine dye from aqueous solution by heterogeneous Fenton-like process. As-synthesized sample was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and N2 adsorption–desorption isotherm. The results indicated that iron impregnation (7 wt.%) did not significantly change specific area but it leads to a clear change in the porous structure of silica. The effects of different reaction parameters such as initial solution pH, initial H2O2 concentration, and additive on the degradation of tartrazine were investigated. The optimal reacting conditions were found to be initial solution pH 3.0, the H2O2 concentration of 12 mM, at a temperature of 30 oC with a dosage of catalyst 50 mg and an initial dye concentration 50 mg/L. Under optimal condition, 98.5% degradation efficiency of tartrazine was obtained within 80 min of reaction. The as-synthesized Fe2O3/SiO2 composite exhibited much better catalytic ability than commercial Fe2O3, as-synthesized Fe2O3, physical mixture Fe2O3/SiO2 under the same experimental condition. In addition, the effects of NaCl and EDTA in the degradation of dye and reaction mechanism were investigated. Keywords. Heterogeneous fenton, composite, Fe2O3/SiO2, tartrazine, degradation